If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(1 + 7p) = 8p + -40 (1 * 2 + 7p * 2) = 8p + -40 (2 + 14p) = 8p + -40 Reorder the terms: 2 + 14p = -40 + 8p Solving 2 + 14p = -40 + 8p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-8p' to each side of the equation. 2 + 14p + -8p = -40 + 8p + -8p Combine like terms: 14p + -8p = 6p 2 + 6p = -40 + 8p + -8p Combine like terms: 8p + -8p = 0 2 + 6p = -40 + 0 2 + 6p = -40 Add '-2' to each side of the equation. 2 + -2 + 6p = -40 + -2 Combine like terms: 2 + -2 = 0 0 + 6p = -40 + -2 6p = -40 + -2 Combine like terms: -40 + -2 = -42 6p = -42 Divide each side by '6'. p = -7 Simplifying p = -7
| -12=4(u-2) | | t^2+1= | | 12x-4-2x=6 | | 3(x+1)-7=2-5(x-2) | | -3(k+4)=-36 | | 4n-9=2n-1 | | 3+m=7-m | | 3t+1=0 | | -3x+12-4x=-5x+16 | | 16+x=35 | | 4.9X^2+21X-300=0 | | -12=-7(u-2) | | 12w+4(6-w)=5x+17 | | 7x-2y=2x+9y | | -8x-28=-(6-3x) | | -85+5x+x=71 | | 12x-5y=-40 | | -3x+12-4x=5x+16 | | 4(3m+4)-(14-4m)=2[4(2+m)-(1-m)] | | 7(x+4)=-8-5x | | Ax+bx-12=-8 | | 3x-7+4x-8=20 | | k-4=-15 | | 14b-21=-12 | | p^2+28p=-33 | | 3x+12x-65=115 | | -3x+12-14x=5x+16 | | -31=2.5=4.5 | | -4y^2+16y=-180 | | 40-6x=-8(x-7)+4x | | -12=-2(u-2) | | s-7fors=8 |